Optimalisasi Pertumbuhan dan Hasil Tanaman kucai (Allium Tuberosum) dengan Menggunakan Biochar Tongkol Jagung dan Kitosan sebagai Media Tanam - Ananda, Rizki; Titisari, Prima Wahyu (Jurnal Ilmiah Pertanian ( JIPERTA), 2026)
In addition to being used as a vegetable, chives are also used in the health sector as a pharmaceutical ingredient because they are antibacterial, including allicin, triterpenoids, flavonoids and saponins, and contain antioxidants that can ward off free radicals. Thus, chives are believed to have benefits for curing diseases such as cancer, hypertension, lowering blood sugar, stimulating appetite, dissolving kidney stones and lowering high blood pressure. Planting media and fertilizer use are one of the main factors that can affect growth, because this is a source of nutrients for plants. This study aims to determine the combination of corn cob biochar and chitosan planting media on the growth and yield of kucai. The method used is a Factorial Completely Randomized Design with two factors: Combination of PMK + Corn Cob Biochar planting media (PMK 1,500g, 1,200g + 300g, 900g + 600g, 600g + 900g) and Chitosan fertilizer dose (0, 4, 8-12 g/planting media). The parameters observed included plant height, number of leaves per clump, wet weight per clump and root volume. Data were analyzed using ANOVA and a further honest significant difference (HSD) test of 5%. The results showed that the combination of PMK 600g planting media + Corn Cob Biochar 900g and Chitosan 12 g/planting media provided significant growth and yield. The use of a combination of PMK 600g planting media + Corn Cob Biochar 900g and Chitosan 12 g/planting media showed potential as an effective organic fertilizer for kucai.